The Critique of the Book Achaemenid Persian Army - Ebrahim Raiygan (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Achaemenid Army is considered an integral part in recognizing the culture and civilization of this period, and the research potential of this part of Achaemenid civilization has led to the writing and publication of such works in this regard. The book of the Achaemenid Persian Army was compiled as such exigency. This effect has influenced the factors affecting the formation, growth, and development as well as the decline of Achaemenid army. The purpose of the present study is to clarify the value of the text of this book in the form of content analysis. In addition to the strengths and research fields, this book has shortcomings that have been addressed in the research. In the overall conclusion, the strengths of the syntactic book and the combination of two categories of sources, including classical historical texts as well as archaeological data along with illustrative illustrations. The book’s weaknesses include inappropriate use of resources, inadequacies of content, some unpredictable claims, and lack of material content. In sum, the present book can be considered as a source of tuition for the Achaemenid history courses, as well as the Achaemenid archeology of the undergraduate and master classes in ancient Iranian history and Historical archaeological period.